Novel oligopeptide nanoprobe for targeted cancer cell imaging - Ding, Wen-Qiang; Qin, Si-Yong; Cheng, Yin-Jia; Ma, Yi-Han; Zhang, Ai-Qing (RSC advances, 2018)
Here we designed and constructed a tryptophan-phenylalanine-phenylalanine-tryptophan (WFFW) tetrapeptide, which generated photostable and tunable fluorescence emission signals from 340 nm to 500 nm. The WFFW tetrapeptide could self-assemble into a spherical nanostructure with enhanced fluorescence intensity. Driven by π–π stacking and hydrogen bond interaction, WFFW co-assembled with arginine-glycine-aspartic acid (RGD) modified WFFW to form a cancer-targeted fluorescent nanoprobe, which could selectively image the cancer cells.